2018
DOI: 10.1021/acs.jproteome.8b00625
|View full text |Cite
|
Sign up to set email alerts
|

Specific Enrichment and Proteomics Analysis ofEscherichia coliPersisters from Rifampin Pretreatment

Abstract: Bacterial persisters, a dormant and multidrug tolerant subpopulation that are able to resuscitate after antibiotic treatment, have recently received considerable attention as a major cause of relapse of various infectious diseases in the clinic. However, because of their low abundance and inherent transience, it is extremely difficult to study them by proteomics. Here we developed a magnetic-beads-based separation approach to enrich Escherichia coli persisters and then subjected them to shotgun proteomics. Rif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 83 publications
3
41
1
Order By: Relevance
“…By inhibiting the activity of ribosomes, we have developed means to convert E. coli cells into a 20 population that consists solely of persister cells (6) so that insights may be made about persister cell resuscitation. Using this approach, which has been verified by six independent labs to produce bona fide persister cells (7)(8)(9)(10)(11)(12), we have shown that persister cells resuscitate rapidly primarily in response to external signals (13), such as fresh nutrients, rather than stochastically (14). Critically, persister cell resuscitation is heterogeneous and depends on the number of active ribosomes; once a threshold of active ribosomes is reached, persister cells elongate and divide (13).…”
Section: Introductionmentioning
confidence: 71%
“…By inhibiting the activity of ribosomes, we have developed means to convert E. coli cells into a 20 population that consists solely of persister cells (6) so that insights may be made about persister cell resuscitation. Using this approach, which has been verified by six independent labs to produce bona fide persister cells (7)(8)(9)(10)(11)(12), we have shown that persister cells resuscitate rapidly primarily in response to external signals (13), such as fresh nutrients, rather than stochastically (14). Critically, persister cell resuscitation is heterogeneous and depends on the number of active ribosomes; once a threshold of active ribosomes is reached, persister cells elongate and divide (13).…”
Section: Introductionmentioning
confidence: 71%
“…The persister cells generated in this way have been (i) confirmed eight ways (19), (ii) used to determine that persister cells wake via ribosome activation (19) and chemotaxis (20), (iii) used to show that the cells capable of resuscitation in a viable but not culturable 95 population are equivalent to persister cells (15), (iv) used to identify compounds that kill persister cells (27), and (v) used to show that the alarmone ppGpp directly creates persister cells by stimulating ribosome dimerization (16). In addition, our method to generate a high population of persister cells has been utilized by at least six independent groups (28)(29)(30)(31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
“…Faced with environmental challenges such as antibiotics, stresses and nutrient deficiency, bacteria can adjust the cellular metabolism in a timely manner to form dormant persister cells, which can tolerate high stress levels and bactericidal effect of antibiotics (5, 6, 65). Previous studies have shown that many metabolic pathways such as carbohydrate metabolism, lipid, nucleotide and amino acid metabolism are involved in the formation of persisters (66, 67). Based on the transcriptomics and metabolomics analyses, we systematically analyzed the pathways by which RpvA could regulate the metabolism of S. aureus (Figure 14).…”
Section: Discussionmentioning
confidence: 99%